Ribosomal Protein L13 Participates in Innate Immune Response Induced by Foot-and-Mouth Disease Virus - Guan, Junyong; Han, Shichong; Wu, Jin’en; Zhang, Yun; Bai, Manyuan; Abdullah, Sahibzada Waheed; Sun, Shiqi; Guo, Huichen (Frontiers in Immunology, 2021)
In addition to ribosomal protein synthesis and protein translation, ribosomal proteins also participate in tumorigenesis and tumor progression, immune responses, and viral replication. Here, we show that ribosomal protein L13 (RPL13) participates in the antiviral immune response induced by foot-and-mouth disease virus (FMDV), inhibiting FMDV replication. The overexpression of RPL13 promoted the induction and activation of the promoters of the nuclear factor-κB (NF-κB) and interferon-β (IFN-β) genes, and the expression and protein secretion of the antiviral factor IFN-β and proinflammatory cytokine interleukin-6 (IL-6). The knockdown of RPL13 had the opposite effects. We also found that the FMDV 3Cpro protease interacts with RPL13, and that its activity reduces the expression of RPL13, thus antagonizing the RPL13-mediated antiviral activity. This study extends our knowledge of the extraribosomal functions of ribosomal proteins, also provides new scientific information on cellular antiviral defenses and virus-antagonizing mechanisms.